Les signaux précoces de l’agir délinquant fréquent - Farrington, David (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1986)
A great deal is known about the early precursors of offending in general, but much less is known about early factors which discriminate between high rate and low rate offenders. Childhood antisocial behaviour, criminal parents and siblings, indicators of social deprivation such as low income, and low intelligence and attainment predict both offending and high rate offending. Many of the future chronic offenders could have been predicted by these factors at the time of their first conviction. However, child rearing factors such as poor parental supervision, harsh or erratic parental discipline, and parental conflict are excellent predictors of offending in general but not of high rate as opposed to low rate offending. Little is known about protective factors which might prevent high risk children from becoming high rate offenders.